The Role of Creative Work Environment Mediation and Gender Moderation in the Influence of Charismatic Leadership and Innovation Culture on Public Organization Performance - Adnan, Ahmad Zaelani (Universitas Brawijaya, Indonesia, 2025)
Bureaucratic transformation in the public sector requires inspirational leadership, an innovative organizational culture, and a work environment that supports creativity to respond to digitalization challenges and increase public expectations. This study aims to analyze the influence of charismatic leadership and innovation culture on public organization performance by including a creative work environment as a mediating variable and Gender Perspective in Leadership as a moderating variable. The study uses a quantitative approach with a descriptive-verificative design, involving 200 civil servants (PNS) in the Regional Apparatus Organization (OPD) of Indramayu Regency, selected through purposive sampling. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM) with SmartPLS 4. The results show that an innovation culture significantly positively affects organizational performance. In contrast, charismatic leadership has a significant but negative effect, suggesting that a leader's dominance can suppress employee initiative if not balanced by participation. A creative work environment served as a partial mediator, strengthening the contribution of innovation culture to performance and channeling the influence of charismatic leadership in a more constructive manner. In addition, Gender Perspective in Leadership played a moderating role in different directions: female employees tended to be more responsive to a supportive charismatic leadership style and a collaborative innovation culture. In contrast, male employees prioritized clarity of structure and rules. These findings emphasize the importance of inclusive and gender-sensitive leadership strategies, strengthening a targeted innovation culture, and creating a sustainable, creative work environment to improve the performance of local bureaucracies in the era of reform and digitalization.